Explaining Academic Interest in Crowdfunding as a Research Topic. (9th March 2021) - Le Pendeven, Benjamin; Bardon, Thibaut; Manigart, Sophie
Abstract: Crowdfunding research has grown exponentially since the first academic papers in the field were published in 2013. This interpretivist study attempts to explain why academics worldwide have chosen to study crowdfunding. As no explicit theories currently exist to guide our research, we have relied on schooling and management fashion theories. Based on interviews with 30 crowdfunding scholars, we develop a model which interprets the underlying reasons why academics have chosen this research topic. Our results show that, beyond scientific reasons, career and socio‐psychological reasons also explain why academics have chosen to research crowdfunding. By documenting both the scientific and non‐scientific reasons why researchers study a certain topic, our findings contribute to the knowledge about the rationales behind scientific development in the fields of management, entrepreneurial finance and entrepreneurship.